Occurrence of selected pharmaceuticals at drinking water purification plants in Japan and implications for human health. (1st June 2015) - Simazaki, Dai; Kubota, Reiji; Suzuki, Toshinari; Akiba, Michihiro; Nishimura, Tetsuji; Kunikane, Shoichi
Abstract: The present study was performed to determine the occurrence of 64 pharmaceuticals and metabolites in source water and finished water at 6 drinking water purification plants and 2 industrial water purification plants across Japan. The analytical methods employed were sample concentration using solid-phase extraction cartridges and instrumental analysis by liquid chromatography with tandem mass spectrometry (LC–MS/MS), liquid chromatography with mass spectrometry (LC/MS), or trimethylsilyl derivatization followed by gas chromatography with mass spectrometry (GC/MS). Thirty-seven of the 64 target substances were detected in the source water samples. The maximum concentrations in the source water were mostly below 50 ng/L except for 13 substances. In particular, residual concentrations of iopamidol (contrast agent) exceeded 1000 ng/L at most facilities. Most of the residual pharmaceuticals and metabolites in the source water samples were removed in the course of conventional and/or advanced drinking water treatments, except for 7 pharmaceuticals and 1 metabolite, i . e ., amantadine, carbamazepine, diclofenac, epinastine, fenofibrate, ibuprofen, iopamidol, and oseltamivir acid. The removal ratios of the advanced water treatment processes including ozonation and granular activated carbon filtration were typically much higher than those of the conventional treatment processes. The margins of exposure estimated by the ratio of daily minimum therapeutic dose to daily intake via drinking water were substantial, and therefore the pharmacological and physiological impacts of ingesting those residual substances via drinking water would be negligible. Graphical abstract: Highlights: The occurrence of 64 pharmaceuticals and metabolites in drinking water was investigated. Thirty-seven substances were detected from source water samples. Eight substances were detected in finished water samples. Elimination was not efficient by the conventional water treatment processes. The health impacts of the residual pharmaceuticals in drinking water would be negligible.